Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

La collaboration à travers les différences : quelques réflexions sur les émotions et la pratique politique - Narayan, Uma (Canadian Journal of Women and the Law, 1993)
Uma Narayan tente de clarifier le contenu de la notion féministe de "privilège épistemique des opprimé-es". Elle soutient que le privilege épistémique des "initié-es" opprimé-es concernant leur oppression suscite des problèmes de dialogue et de politique de coalition avec les "non-initié-es" qui eux, ne subissant pas cette oppression, n'arrivent pas à se réconcilier au privilege épistémique des initié-es. Elle analyse concrètement comment les non-initié-es peuvent par inadvertance blesser les initié-es, et elle propose des moyens permettant de minimiser ces problèmes.
Keywords: approches et analyses; discipline; injustices épistémiques; intersectionnalité; inégalités; militance; privilèges; ressource en ligne; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; émotions; épistémologie

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences